Sense-making and problem-solving approaches as applied to the information needs of history researchers - San Pedro, Marjorie Rose S. (Institute of Library and Information Science, University of the Philippines Diliman, 2003)
Data-centered information systems prove to be ineffectual in maximizing the potential of an information system and it fails to meet the growing information needs of today's society. To produce user-centered information systems, more in-depth inputs about the users and their needs are essential.